One Hundred Consecutive Neutropenic Febrile Episodes Demonstrate That CXCR3 Ligands Have Predictive Value in Discriminating the Severity of Infection in Children with Cancer - Małgorzata Nowak; Katarzyna Bobeff; Justyna Walenciak; Julia Kołodrubiec; Krystyna Wyka; Wojciech Młynarski; Joanna Trelińska (MDPI AG, 2022)
This study assesses the value of the CXCR3 ligands CXCL9/MIG, CXCL10/IP-10 and CXCL11/I-TAC when used to supplement the standard infection markers C-reactive protein (CRP) and procalcitonin (PCT) in the diagnostic algorithm of neutropenic fever in children with cancer. The concentration of CRP, PCT and chemokines was determined during the first hour of fever and 12-24 h afterwards in pediatric oncology patients with neutropenia. Among 100 consecutive febrile episodes in neutropenic patients, 34 cases demonstrated fever of unknown origin (FUO) (group A), 47 demonstrated mild clinically or microbiologically proven infection (Group B) and 19 severe infection (Group C). Significantly higher PCT-1 levels were found in group C (0.24 ng/mL) vs. group A (0.16 ng/mL), and PCT-2 in group C (1.2 ng/mL) vs. A (0.17 ng/mL), and in C vs. B (0.2 ng/mL). Chemokine concentrations (I-TAC-1, IP-10-1, IP-10-2) were significantly lower in Group A vs. B+C; I-TAC 1: 48.64 vs. 70.99 pg/mL, p = 0.03; IP-10 1: 59.95 vs. 96.84 pg/mL, p = 0.04; and IP-10 2: 102.40 vs. 149.39 pg/mL, p = 0.05. The selected pro-inflammatory chemokines I-TAC and IP10 might help to distinguish cancer patients with febrile neutropenia with the highest risk of infection. Although procalcitonin could serve as a marker of a high risk of infection, its delayed response diminishes its usefulness.